Diseño de un sistema de producción de productos derivados del cacao en la provincia de Esmeraldas - Lastra Mina, Kenia Estefanía (2023)
This research project details the design of a production system for cocoa-derived products in the province of Esmeraldas. It begins with the description of each of the stages involved in the transformation of the cocoa bean into paste and butter, from the establishment of soil characteristics for planting to the packaging process, once the beans have passed the drying stage. , ground and pressed. Cocoa production in Ecuador increases each year with a growth of 4.95%, reaching a national production of 543,547 tons and a value per ton of $2,551, with the aim of increasing in the coming years.